Terminal alliance - Hines, Jim C. (Hines, Jim C. Janitors of the post-apocalypse, 2017)
"The Krakau came to Earth to invite humanity into a growing alliance of sentient species. But they hadn't counted on a mutated plague wiping out half the human population, turning the rest into shambling, near-unstoppable animals, and basically destroying human civilization. You know, your standard apocalypse. The Krakau's first impulse was to turn around and go home. (After all, it's hard to have diplomatic relations with mindless savages who eat your diplomats.) Their second impulse was to try to fix us. Now, a century later, human beings might not be what they once were, but at least they're no longer trying to eat everyone. Mostly."--Jacket flap.